2018
DOI: 10.5530/jyp.2018.10.25
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Evaluation of Cutaneous Adverse Drug Reactions (CADRs) Due to Antibiotics Using Naranjo Adverse Drug Reactions (ADRs) Probability Scale

Abstract: Cutaneous adverse drug reactions (CADRs) have been found to be one of the most common adverse drug reactions (ADRs) in many studies. There is no common globally accepted tool for causality grading of ADRs to be utilized in pharmacovigilance programs. Our study aimed to show the coincidence of Naranjo method in evaluating clinically diagnosed cutaneous adverse drug reactions in Sudanese patients. The causality of the CADRs was retrospectively evaluated by using Naranjo's ADR probability scale. The study include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Indeed, items 6 to 10 were scored “do not know” for most drugs because data were not most often available. This issue was raised by other authors 41,42…”
Section: Limitations Of the Studymentioning
confidence: 88%
“…Indeed, items 6 to 10 were scored “do not know” for most drugs because data were not most often available. This issue was raised by other authors 41,42…”
Section: Limitations Of the Studymentioning
confidence: 88%
“…A retrospective descriptive study in a teaching hospital in Sudan found significant numbers of severe cADRs involving various antibiotics where ciprofloxacin was the greatest offender (41.46% of FDE, EM-Major, SJS and TEN). Other ABs or AMs involved were artesunate (12.2% of EM-Major, SJS, TEN), penicillin (7.32% of EM-Major, SJS), sulfamethoxazole-trimethoprim (7.32% of SJS, TEN, SJS/TEN overlap), norfloxacin (7.32% of TEN), amoxycillin (4.88% of SJS, TEN), ceftriaxone (4.88% of SJS, TEN) and ampicillin-cloxacillin, amoxicillin-clavulanic acid, Fansidar (sulfadoxine and pyrimethamine), erythromycin, clarithromycin and tetracycline caused 2.4% each of SJS, TEN and EM-Major reactions [101]. There is a wide variation in the frequency of various types of cADRs in the studies reviewed.…”
Section: Juniper Online Journal Of Dermatology and Cosmeticsmentioning
confidence: 99%
“…A retrospective descriptive study in a teaching hospital in Sudan found significant numbers of severe cADRs involving various antibiotics where ciprofloxacin was the greatest offender (41.46% of FDE, EM-Major, SJS and TEN). Other ABs or AMs involved were artesunate (12.2% of EM-Major, SJS, TEN), penicillin (7.32% of EM-Major, SJS), sulfamethoxazole-trimethoprim (7.32% of SJS, TEN, SJS/TEN overlap), norfloxacin (7.32% of TEN), amoxycillin (4.88% of SJS, TEN), ceftriaxone (4.88% of SJS, TEN) and ampicillin-cloxacillin, amoxicillin-clavulanic acid, Fansidar (sulfadoxine and pyrimethamine), erythromycin, clarithromycin and tetracycline caused 2.4% each of SJS, TEN and EM-Major reactions [101]. There is a wide variation in the frequency of various types of cADRs in the studies reviewed.…”
Section: Juniper Online Journal Of Dermatology and Cosmeticsmentioning
confidence: 99%